Essential Second Modules - Ahmed, Ghaleb (Iraqi Journal of Science, 2019)
M is viewed as a right module over an arbitrary ring R with identity. The essential second modules is defined in this paper. We call M is essential second when for any a bilongs to R, either Ma = 0 or Ma <e M. Number of conclusions are gained and some connections between these modules and other related modules are studied.